DEVELOPMENT OF ANDROID-BASED AUGMENTED REALITY LEARNING MEDIA ON THE INTRODUCTION OF GEOMETRY MATERIAL FOR KINDERGARTEN STUDENTS - Taufik Rachman; Hilal Istafaina Awab (Computer Science Department, Malang National Institute of Technology, 2024)
This research aims to develop an application that can help kindergarten students in understanding space buildings in the introduction of Geometry subject. Research and development of the application used Research and Development (R&D) method that aim to produce certain products and test the effectiveness of these products. The product was developed using the ADDIE Process model method. The ADDIE software development model has five stages: analysis, design, development, implementation, and evaluation. This geometry learning media application using Unity 3D was tested through the Black Box Testing method and questionnaire testing. This learning application can help teachers in teaching the material of geometry through media applications to contribute a more interactive learning process.